Genetic characterization of mitochondrial genome of the small intestinal fluke, Haplorchis taichui (Trematoda: Heterophyidae), Vietnamese sample - Hòa, Lê Thanh; Khuê, Nguyễn Thị; Nga, Nguyễn Thị Bích; Roan, Đỗ Thị; Dũng, Đỗ Trung; Xuyến, Lê Thị Kim; Hương, Đoàn Thị Thanh (Vietnam Journal of Biotechnology, 2016)
The small intestinal fluke, Haplorchis taichui Nishigori, 1924, belonging to genus Haplorchis (family Heterophyidae, class Trematoda, phylum Platyhelminthes), is a zoonotic pathogen causing disease in humans and animals. Complete mitochondrial genome (mtDNA) of H. taichui (strain HTAQT, collected from Quang Tri) was obtained and characterized for structural genomics providing valuable data for studies on epidemiology, species identification, diagnosis, classification, molecular phylogenetic relationships and prevention of the disease. The entire nucleotide mtDNA sequence of H. taichui (HTAQT) is 15.119 bp in length, containing 36 genes, including 12 protein-coding genes (cox1, cox2, cox3, nad1, nad2, nad3, nad4L, nad4, nad5, nad6, atp6 and cob); 2 ribosomal RNA genes, rrnL (16S) and rrnS (12S); 22 transfer RNA genes (tRNA or trn), and a non-coding region (NR), divided into two sub-regions of short non-coding (short, SNR) and long non-coding (long, LNR). LNR region, 1.692 bp in length, located between the position of trnG (transfer RNA-Glycine) and trnE (Glutamic acid), contains 6 tandem repeats (TR), arranged as TR1A, TR2A, TR1B, TR2B, TR3A, TR3B, respectively. Each protein coding gene (overall, 12 genes), ribosomal rRNA (2 genes) and tRNA (22 genes) were analyzed, in particular, protein-coding genes were defined in length, start and stop codons, and rRNA and tRNA genes for secondary structure